PENERAPAN PARLIAMENTARY THRESHOLD DALAM PEMBENTUKAN PEMERINTAHAN PRESIDENSIAL YANG STABIL MENURUT UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - Iswandari, Bunga Asoka; Isharyanto, Isharyanto (Department of the Constitutional Law, Faculty of Law Universitas Sebelas Maret, 2019)
This study aims to examine the Application of Treshold Parliamentary in the Establishment of Stable Presidential Governments according to the 1945 Constitution of the Republic of Indonesia. This research is normative legal research, the types and sources of data used are secondary data consisting of primary legal materials and secondary legal materials related to the discussion. The nature of the research used is descriptive research using the Law approach, case approach, historical approach, comparative approach, and conceptual approach. The legal material analysis technique used is deduction with the syllogism method, meaning that the analysis of legal material prioritizes thinking logically so that it finds the cause and effect that will occur. The results of the study show how the influence of the implementation of the parliamentary threshold in the Indonesian electoral system towards the establishment of a stable presidential government adopted by Indonesia in accordance the 1945 Constitution of the Republic of Indonesia.